Bureaucracy in public schools – waste of time, offence to the self or professional Challenge - Limborg, Hans Jørgen; Albertsen, Karen; Jensen, Maya Flensborg (Tidsskrift for Arbejdsliv, 2012)
In recent years teachers and managers in the Danish Public School have been exposed to an increased requirement to document and record issues and elements in their work. This tendency to increase demands for registration is experienced generally across the public sector, and is related to the New Public Management governance paradigm that was predominant in Danish regulation of the welfare and teaching sectors in the first decade of this century. This form of regulation is argued to have created an imbalance in the development of public service between the bureaucratic system thinking and the experience and knowledge that has characterized the professionals in the welfare sector. Documentation and registration can be experienced as a burden that takes time from the core task, but it can also contribute to stress because – and following Norbert Semmer’s concept – it is potentially offensive to self-esteem if tasks irrelevant to the core task are perceived as illegitimate. The article describes the concepts of ‘student plans’ and ‘quality reports’ as an example of such control systems that can create stress among the teacher and school leaders. However it depends on whether these control demands are experienced as offensive to the professional self-esteem or if the school teachers and management are able to transform the demands into ‘manageable educational tools’ that are relevant to the task of teaching. This response which is seen at some of the schools in seven case studies may be an element in creating new ways of public management and regulation based upon the development of dialogue, and resulting in less stressful work relations. The article argues that there is an important difference between control and documentation that is aimed at the relation between what you perform and what you achieve and documentation of specific results that are compared with predetermined goal or with the performance of other schools. The first type is easily transformed into relevant tools, whereas the second type holds the risk of being experienced as irrelevant or even worse as offensive.